Distributed generation system using parallel inverters supplied by unstable DC source - Younis, M.A.A.; Rahim, N.A.; Mekhilef, Saad (2009)
This study presents the analysis and design of distributed generation system. The system consists of a full-bridge DC-DC converter, two units of three-phase inverters connected in parallel and a controller. Two units of conventional three-phase DC-AC inverters connected in parallel with series resistors were added to the inverter output to maintain the same current in each inverter and to minimize the circulating current in the parallel inverters. High frequency third harmonic injection PWM (THIPWM) was employed to reduce the total harmonic distortion and to make maximum use of the DC bus voltage. The generation of control algorithm for three-phase inverter is implemented in Digital Signal Processing (DSP) boards. The THIPWM have been done such that the inverter output voltage is synchronized with the grid voltage thus making the inverter suitable for grid connection. The three-phase inverter operates with a total harmonic distortion of less than 2 on output voltage and current signals. Experimental results are shown validate the proposed system. A full distributed generation system has been implemented and tested, the testing of the system proves that the system operates with minimum circulating current on the parallel connected inverter and minimum harmonic distortion on the inverter output voltage and current.